O outro lado do desenvolvimento (in)sustentável - Carneiro, Maria Eduarda Congentino (2024)
The present research investigated the concept of sustainable development, its motivations, and limitations, as well as its relationship with the historical appropriation of Brazilian territory, focusing on the traditional caiçara community of Enseada da Baleia, located on the southern coast of São Paulo, on the municipality of Cananéia. The region was chosen due to the severe recent environmental impacts that have intensely affected the local traditional communities. The research sought to understand how these extreme environmental events influence the practices of these communities and their strategies of resistance. To this end, an analysis was conducted in two stages: the first focused on understanding the conditions of sustainable development in Brazil and its connection to the historical appropriation of land, and the second dedicated to the historical and contemporary analysis of the Enseada da Baleia community, aiming to demonstrate that land and territory are not limited to market values but are instead symbols of belonging, identity, ancestry, and resistance. The methodology employed was exploratory qualitative, with focus groups, oral history interviews, participant observation, community visits, and bibliographic systematization supported by various authors, including Bruno Latour (2019), Warren Dean (1996), Ulrich Beck (2010), Saskia Sassen (2016), and Malcom Ferdinand (2021). The research showed that the process of territorial domination in Brazil is rooted in a colonialist logic, perpetuated through agribusiness and mining, and highlighted the forms of resistance that arise in traditional communities in response to these dynamics. The study contributes to the understanding of territorial disputes and the role of traditional communities in preserving natural resources